2016
DOI: 10.1097/md.0000000000004093
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of off- and on-hours admission in ST-segment elevation myocardial infarction patients undergoing primary percutaneous coronary intervention

Abstract: Studies evaluating the outcomes of patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI) are scarce, particularly in China. The purpose of present study was therefore to compare the impact of off-hours and on-hours admission on clinical outcomes in STEMI patients from China.We retrospectively analyzed 1594 patients from 4 hospitals. Of these, 903 patients (56.65%) were admitted during off-hours (weekdays from 18:00 to 08:00, weekends and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Several factors may contribute to the association between off-hours presentation and high short-term mortality. Off-hours presentation is associated with adverse baseline characteristics, such as a higher prevalence of cardiac risk factors and lower ejection fraction; previous studies, including ours, have also found that patients who presented during off-hours had more severe symptoms than those who presented during on-hours[ 16 , 28 , 30 ], which may partially explain the increased short-term mortality. Another potential contributor is lower availability of PPCI, according to the result of our subgroup analysis.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Several factors may contribute to the association between off-hours presentation and high short-term mortality. Off-hours presentation is associated with adverse baseline characteristics, such as a higher prevalence of cardiac risk factors and lower ejection fraction; previous studies, including ours, have also found that patients who presented during off-hours had more severe symptoms than those who presented during on-hours[ 16 , 28 , 30 ], which may partially explain the increased short-term mortality. Another potential contributor is lower availability of PPCI, according to the result of our subgroup analysis.…”
Section: Discussionmentioning
confidence: 47%
“…All the studies were published in English, except two, which were in Portuguese[ 26 , 27 ]. All patients were from a prospective clinical registry cohort, except two, which were from a retrospective cohort[ 9 , 28 ]. All studies retrospectively analyzed the collected data.…”
Section: Resultsmentioning
confidence: 99%
“…Data were presented as mean±standard deviation for continuous variables and percentages for categorical variables. Logarithmic transformation of the echocardiography data was applied to fulfill the requirement of normal distribution based on the results of Kolmogorov-Smirnov test [ 24 ]. Differences among the groups were analyzed using analysis of variance or chi-square analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were evaluated from the discharged day until death or December 2016, from at least 1 of the following 3 methods: medical records, telephone contact, and outpatient visitation as described previously. [ 25 ] A 12-lead electrocardiogram and/or 24-hour ambulatory electrocardiogram monitoring were made for the clinical assessment. Our primary endpoint was major adverse cardiac events (MACEs), a composite of all-cause mortality, stroke and unplanned hospitalization.…”
Section: Methodsmentioning
confidence: 99%